Leproma Presenting as a Nasal Cavity Mass. Issue 8 (November 2015) - Kim, Jong Seung; Kwon, Sam Hyun; Shin, Jin Yong
Abstract : Abstract: Leprosy is a rare disease and unfamiliar to many people. A 55-year-old woman was presented to our hospital complaining of nasal obstruction and anosmia. Nasal endoscopic examination revealed reddish-colored exophytic, nonulcerative masses in both nasal cavities. The authors performed endoscopic sinus surgery which involved endoscopic mass removal and synechiolysis. A biopsy sample stained with acid-fast stain and a rapid silver stain showed numerous filamentous organisms infiltrating macrophages, consistent with lepromatous leprosy. The patient was treated with a triple drug regimen of rifampin and dapsone with clofazimine. Herein, the authors present a case of nasal leproma as a differential diagnosis of a nasal cavity mass.